Sistem Informasi Pemesanan Tiket Pada PERUM DAMRI Ende - Gedofrida Ludfina Bhiju; L.B. Finansius Mando; Elvira Esperanza Sala (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The development of information technology encourages public service agencies to improve the quality of service through the use of integrated information systems. PERUM DAMRI Ende as a provider of passenger transportation services, still faces problems in delivering information on schedules, routes, fares, and vehicle data management that has not been optimally integrated, thus causing uncertainty for service users. This study aims to design and build a Passenger Transport Vehicle Information System at PERUM DAMRI Ende to improve fleet data management efficiency, route scheduling, and customer information access. The research method used is a case study with a qualitative descriptive approach. System development is carried out using the Waterfall method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The system is built as a web-based application using the PHP programming language and a MySQL database, and tested using the Black-Box Testing method. The results of the study are expected to help PERUM DAMRI Ende manage vehicle and schedule data more effectively, improve service quality, and provide the public with greater convenience in obtaining passenger transportation information.